2022
DOI: 10.18502/kls.v7i2.10357
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Positive Thinking in Nursing Students During the Covid-19 Pandemic

Abstract: The Covid-19 pandemic has resulted in many new policies being issued to prevent an increase in the number of transmissions. One of these policies is remote online learning. This is a stressor for students of the Faculty of Nursing, Padjadjaran University because of the adaptation in the learning system. These stressors need to be handled with effective coping strategies, two of which can be religiosity and positive thinking. Both of these are internal factors that are personal to each individual, including stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…By nurturing their psychological immune system or self-defense mechanisms, married women can attain physical, emotional, social, and environmental well-being, contributing to quality life. Yosep et al (2022) found that religiosity is related to positive thinking, which serves as an indicator to the psychological immune system. Furthermore, Jahromi et al (cited in Yosep et al, 2022) found positive thinking effective for enhancing work-related quality of life.…”
Section: Path Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…By nurturing their psychological immune system or self-defense mechanisms, married women can attain physical, emotional, social, and environmental well-being, contributing to quality life. Yosep et al (2022) found that religiosity is related to positive thinking, which serves as an indicator to the psychological immune system. Furthermore, Jahromi et al (cited in Yosep et al, 2022) found positive thinking effective for enhancing work-related quality of life.…”
Section: Path Coefficientmentioning
confidence: 99%
“…Yosep et al (2022) found that religiosity is related to positive thinking, which serves as an indicator to the psychological immune system. Furthermore, Jahromi et al (cited in Yosep et al, 2022) found positive thinking effective for enhancing work-related quality of life.…”
Section: Path Coefficientmentioning
confidence: 99%
See 1 more Smart Citation